2020
DOI: 10.1787/3f8a12c6-en
|View full text |Cite
|
Sign up to set email alerts
|

Policies for Switzerland’s ageing society

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. 2  ECO/WKP(2020)8 POLICIES FOR SWITZERLAND'S AGEING SOCIETY Unclassified OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s). Worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, current demographic projections reveal that the global population aged 65 years and older will substantially increase from 9% to 16% by 2050 [36]. This could potentially result in a much larger temperature-related burden since older adults are particularly more at risk of temperature-related health effects [37]. Additionally, previous studies on cold-related mortality projections generally observed a decrease in cold-related mortality mainly driven by the reduction in cold days [19,23,25,30,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, current demographic projections reveal that the global population aged 65 years and older will substantially increase from 9% to 16% by 2050 [36]. This could potentially result in a much larger temperature-related burden since older adults are particularly more at risk of temperature-related health effects [37]. Additionally, previous studies on cold-related mortality projections generally observed a decrease in cold-related mortality mainly driven by the reduction in cold days [19,23,25,30,38].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings indicate that ageing over the past 50 years has resulted in a significant rise in cold-and heat-related mortality in Switzerland [29]. Hence, it becomes crucial to account for socioeconomic scenarios, given the projected increase in the proportion and size of older adults (>65 years) from 16% to 30% by 2060 in Switzerland [37]. Lastly, heat-and cold-related mortality risk has been found to be highly variable across small regions in Switzerland [39].…”
Section: Introductionmentioning
confidence: 99%
“…For example, current demographic projections reveal that the global population aged 65 years and older will substantially increase from 9-16% by 2050. 36 This could potentially result in a much larger temperature-related burden since older adults are particularly more at risk of temperature-related health effects 37 . Additionally, previous studies on cold-related mortality under different climate-change scenarios generally observed a decrease in cold-related mortality 19,23,25,31,38 .…”
Section: Introductionmentioning
confidence: 99%
“…However, to date few studies have projected the heat-, and in particular, the cold-related mortality while accounting for population development 19,42,43 . This is particularly relevant as the proportion and size of this extravulnerable sub-population is likely to increase from 16-30% by 2060 in Switzerland 37 .…”
Section: Introductionmentioning
confidence: 99%